Cardiovascular and nervous system changes during meditation - Steinhubl, Steven R.; Wineinger, Nathan E.; Patel, Sheila; Boeldt, Debra L.; Mackellar, Geoffrey; Porter, Valencia; Redmond, Jacob T.; Muse, Evan D.; Nicholson, Laura; Chopra, Deepak; Topol, Eric J. (Frontiers in Human Neuroscience, 2015)
Background: A number of benefits have been described for the long-term practice of meditation, yet little is known regarding the immediate neurological and cardiovascular responses to meditation. Wireless sensor technology allows, for the first time, multi-parameter and quantitative monitoring of an individual's responses during meditation. The present study examined inter-individual variations to meditation through continuous monitoring of EEG, blood pressure, heart rate and its variability (HRV) in novice and experienced meditators. Methods: Participants were 20 experienced and 20 novice meditators involved in a week-long wellness retreat. Monitoring took place during meditation sessions on the first and last full days of the retreat. All participants wore a patch that continuously streamed ECG data, while half of them also wore a wireless EEG headset plus a non-invasive continuous blood pressure monitor. Results: Meditation produced variable but characteristic EEG changes, significantly different from baseline, even among novice meditators on the first day. In addition, although participants were predominately normotensive, the mean arterial blood pressure fell a small (2–3 mmHg) but significant (p < 0.0001) amount during meditation. The effect of meditation on HRV was less clear and influenced by calculation technique and respiration. No clear relationship between EEG changes, HRV alterations, or mean blood pressure during meditation was found. Conclusion: This is the first study to investigate neurological and cardiovascular responses during meditation in both novice and experienced meditators using novel, wearable, wireless devices. Meditation produced varied inter-individual physiologic responses. These results support the need for further investigation of the short- and long-term cardiovascular effects of mental calm and individualized ways to achieve it.